2014
DOI: 10.3402/gha.v7.25484
|View full text |Cite
|
Sign up to set email alerts
|

Gender bias in clinical research, pharmaceutical marketing, and the prescription of drugs

Abstract: This thesis is part of the studies of gender bias in health which together with the paradigm of evidence-based medicine shares the empirical assumption that there are inaccuracies in medical practice, in addition to a lack of rigour and transparency. It worked with the distinction between the concepts of sex and gender and between the concepts of sex-related differences and gender inequalities, in terms of applying a gender perspective in the study design and the subsequent analysis. This PhD review presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
0
20
1
2
Order By: Relevance
“…leading to the mistaken view of men and women as similar (or different) in exposure to risks or in the natural history of disease (.).'' 15 In the first section, we describe sex and gender differences in kidney transplantation and donation. In the second section, we explore sex and gender bias in 3D bioprinting of kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…leading to the mistaken view of men and women as similar (or different) in exposure to risks or in the natural history of disease (.).'' 15 In the first section, we describe sex and gender differences in kidney transplantation and donation. In the second section, we explore sex and gender bias in 3D bioprinting of kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, use of online or web-based tools to aid clinical care is a widespread practice. A study in Sweden related to the follow-up care of chronic heart failure patients found that 67% of health care workers used web-based or online resources, with 74% of respondents reporting positive attitudes toward application of information, communication and technology (ICT) in health care; interestingly, up to 96% were optimistic regarding the future positive contribution of ICT in health care.7 On the African continent, limited access to ICT infrastructure and low rates of computer literacy have been cited as an obstacle towards uptake and utilization of web-based health care resources for clinical decision making and providing health care, especially amongst female health care workers, who form the bulk of the health care workforce in Africa.8 In Rwanda, the national ICT policy encourages the leverage of ICT in all sectors to achieve the Vision 2020 goals to improve the overall health status of the population. This also applies to the health sector where electronic medical records (EMR) and electronic health management information system (EHMIS) technologies to enhance patient care are being rolled out.…”
Section: Introductionmentioning
confidence: 99%
“…Access to health care is often a significant part of election manifestos, and increasing access to information means that people are generally better informed about issues that affect their health. 13 Health systems have had to be responsive to changing health priorities, such as the types of services that need to be covered, the needs of different population groups as population demographic profiles change, 14,15 and the types of treatments that may be considered essential and/or optional. 13 In this article, we explore how the process of engagement with communities can be implemented to inform and enhance health systems and support progress toward UHC.…”
Section: Introductionmentioning
confidence: 99%
“…13 Health systems have had to be responsive to changing health priorities, such as the types of services that need to be covered, the needs of different population groups as population demographic profiles change, 14,15 and the types of treatments that may be considered essential and/or optional. 13 In this article, we explore how the process of engagement with communities can be implemented to inform and enhance health systems and support progress toward UHC. We begin with the assumption that as a constitutional right in most countries, 10 community engagement in the design of health policy and health care is desirable and an important intervention.…”
Section: Introductionmentioning
confidence: 99%